2003
DOI: 10.1177/0022022103257855
|View full text |Cite
|
Sign up to set email alerts
|

Implicit-Explicit Differences in Self-Enhancement for Americans and Japanese

Abstract: Past research on cross-cultural psychology has shown that North Americans have self-enhancing attitudes, evaluating themselves more favorably than others, including friends. The present research identifies a discrepancy — this self-enhancement in relation to friends did not appear when measured implicitly. Using American and Japanese university students as subjects, the present studies investigated responses to explicit (self-report) and implicit measures (the Implicit Association Test) toward three targets: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 40 publications
9
49
0
Order By: Relevance
“…This view is based on the stereotypic dichotomy that individualistic cultures value independence and uniqueness, while collectivistic cultures value interdependence and similarity (Markus & Kitayama, 1991). Use of the Implicit Association Test, however, has demonstrated convincingly that the motive exists in both North America and Japan (Kobayashi & Greenwald, 2003), and these findings concur with other studies conducted with improved methodologies (Brown & Kobayashi, 2002;Kobayashi & Brown, 2003). These studies also question the validity of self-report data about attitudes related to culture.…”
Section: Notessupporting
confidence: 57%
“…This view is based on the stereotypic dichotomy that individualistic cultures value independence and uniqueness, while collectivistic cultures value interdependence and similarity (Markus & Kitayama, 1991). Use of the Implicit Association Test, however, has demonstrated convincingly that the motive exists in both North America and Japan (Kobayashi & Greenwald, 2003), and these findings concur with other studies conducted with improved methodologies (Brown & Kobayashi, 2002;Kobayashi & Brown, 2003). These studies also question the validity of self-report data about attitudes related to culture.…”
Section: Notessupporting
confidence: 57%
“…Other studies, however, have examined self-esteem or self-enhancement from a relational approach. For example, in a laboratory experiment involving pairs of friends, both Japanese and Americans demonstrated implicit positive self-evaluations and explicit negative self-evaluations when making comparisons between self and a close friend of the same gender (Kitayama & Uchida, 2003;Kobayashi & Greenwald, 2003), but the role of positive feedback from others in self-esteem maintenance remains to be demonstrated (in the present study).…”
Section: Cross-cultural Self-evaluation Research In a Relationship Comentioning
confidence: 47%
“…The present study builds on previous work that has considered self-evaluation in a relational context (Dalsky, Gohm, Noguchi, & Shiomura, 2008;Kitayama & Uchida, 2003;Kobayashi & Greenwald, 2003;Muramoto, 2003;Muramoto & Yamaguchi, 1997). It involves a cross-cultural experiment in which two friends were not engaged in competition to test for cultural differences in the effects of positive feedback on selfesteem.…”
Section: Overview and Predictions Of The Present Studymentioning
confidence: 99%
“…Kobayashi and Greenwald (2003) found discrepancies in implicit–explicit references of others and self in Japanese people and their Western counterparts. They also found that for Japanese people, describing oneself as superior to others is less acceptable, whereas in Western cultures, describing oneself as inferior to others is less acceptable.…”
Section: Literature Reviewmentioning
confidence: 91%